Emission patterns of traffic-related metals and associated contamination in road deposited sediment. (1st January 2012) - Pal, Sudip K.; Wallis, Steve G.; Arthur, Scott
Road deposited sediment (RDS) is regarded as sinks for metal pollutants derived from road-traffic that may pose a danger for the nearby water environment. The reported study aims to analyse RDS build-up and associated metal emission patterns using Riccarton Campus of Heriot Watt University, Edinburgh, Scotland as a study site. The RDS samples were collected from four different sites over a four month period to characterise the influence of road lay-out on metal emissions. The metal concentrations associated with the RDS were determined by strong nitric acid digestion and atomic absorption spectrometry. The outcomes of the investigation show highly site-specific variability of the RDS build-up primarily linked to road lay-out, and that road surface conditions and surrounding land use influenced the results. Similarly, irrespective of traffic volume, site attributes were found to be the drivers for the observed differences in metal concentration. Furthermore, a significant proportion of pollutants were found to be associated with finer particles (size < 63 µm) and that RDS exhibited moderate to strong levels of pollution for Zn, Cu and Pb.